Knuth–Bendix completion of theories of commuting group endomorphisms - Stump, Aaron; Löchner, Bernd (Information processing letters, 2006)
Knuth–Bendix completions of the equational theories of k ⩾ 2 commuting group endomorphisms are obtained, using automated theorem proving and modern termination checking. This improves on modern implementations of completion, where the orderings implemented cannot orient the commutation rules. The result has applications in decision procedures for automated verification.